ON THE ISSUE OF THE APPLICATION OF PROCEEDINGS CARRIED OUT IN THE ABSENCE OF THE ACCUSED - Mkrtchyan, Petik (State and Law, 2023)
The article considers the question of whether the procedure of proceedings carried out in the absence of the accused can be applied in criminal cases in which the proceedings were initiated before the entry into force of the norms regulating the said proceedings. The author, based on legislative regulations, judicial practice and opinions expressed in the theoretical literature, proposes a solution that will make possible the uniform application of the law and ensure the unity of practice.